Higher Education - The Weakest Link of the Romanian Competitiveness? - Radu Gheorghiu (Revista de Economie Mondială, 2012)
Higher education plays an increasing role for national competitiveness, fact also acknowledged by its presencs as one of the 12 pillars in the Global Competitiveness Index. From this perspective, Romania provides the image of a rather imature higher education market, chracteristed by dominant low cost services, with limited relevance for the labour market . The article builds a SWOT of the Romania higher education system in view of its contribution to national competitiveness.